Vaccine apartheid: This is not the way to end the pandemic. (21st October 2021) - Lanziotti, Vanessa S; Bulut, Yonca; Buonsenso, Danilo; Gonzalez‐Dambrauskas, Sebastian
Abstract : There are many reasons why the international community as a whole should advocate for COVID‐19 vaccine equity: global economic recession, uncontrolled outbreaks with higher risk of virus variants and persistent unsafe travelling in an era of now vaccine‐preventable cause of death. This inequity is an avoidable threat to global health. Funding agencies, policy makers, drug companies and NGOs among others have the moral duty to end this vaccine apartheid and to make vaccine equity a reality. In this viewpoint, we discuss how inequalities in vaccination access affect a proper control of the pandemic, highlighting specific consequences on child health.